A is for Asylum Seeker: Words for People on the Move / A de asilo: palabras para personas en movimiento - Buff, Rachel Ida (Book collections on Project MUSE., 2020)
A clear and concise A-to-Z of keywords that echo our current human rights crisis. As millions are forced to leave their nations of origin as a result of political, economic, and environmental peril, rising racism and xenophobia have led to increasingly harsh policies. A mass-mediated political circus obscures both histories of migration and longstanding definitions of words for people on the move, fomenting widespread linguistic confusion. Under this circus tent, there is no regard for history, legal advocacy, or jurisprudence. Yet in a world where the differences between "undocumented migrant" and "asylum seeker" can mean life or death, words have weighty consequences. A timely antidote to this circus, A is for Asylum Seeker reframes key words that describe people on the move. Written to correct the de-meaning of terms by rhetoric and policies based on dehumanization and profitable incarceration, this glossary provides an intersectional and historically grounded consideration of the words deployed in enflamed debate. Skipping some letters of the alphabet while repeating others, thirty terms cover everything from Asylum-seeker to Zero Tolerance Policy. Each entry begins with a contemporary or historical story for illustration and then proceeds to discuss the language politics of the word. The book balances terms affected by current political debates--such as "migrant," "refugee," and "illegal alien"--and terms that offer historical context to these controversies, such as "fugitive," "unhoused," and "vagrant." Rendered in both English and Spanish, this book offers a unique perspective on the journeys, histories, challenges, and aspirations of people on the move. Enhancing the book's utility as an educational and organizing resource, the author provides a list of works for further reading as well as a directory of immigration-advocacy organizations throughout the United States.